HARMONIZATION OF TECHNICAL REGULATION AND STANDARDIZATION OF ELECTRIC VEHICLE CHARGING STATIONS IN UKRAINE IN ACCORDANCE WITH EU REQUIREMENTS - BOHOIKO, IHOR; ZAMULKO, ANATOLII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article examines the current state and the need to improve the regulatory and technical framework for electric vehicle charging infrastructure (EVCI) in Ukraine. The study highlights the necessity of harmonizing national standards with the norms and requirements of the European Union to ensure the safe and efficient functioning of charging systems. It analyzes existing technical regulations and harmonized national standards (DSTU EN/IEC) that define the requirements for safety, technical compatibility, metrological accuracy, and electromagnetic compliance of charging equipment. The main configuration standards are outlined, including DSTU EN 62196-3:2019, DSTU EN IEC 61851-1:2021, DSTU EN 61851-23:2015, DSTU EN 61851-24:2015, DSTU HD 60364-7-722:2022, DSTU EN 50620:2021, and DSTU EN 62752:2019. The analysis reveals the need to update and supplement part of these standards to include IEC 62955, EN ISO 15118-20, OCPP 1.6/2.0.1, and the requirements of Regulation (EU) 2023/1804 (AFIR), particularly regarding open communication protocols, interoperability, digital payment integration, and smart charging capabilities. It is emphasized that the Ukrainian regulatory framework only partially correlates with the European one, creating potential interoperability gaps that hinder the integration of Ukrainian charging stations into the single EU market. The article substantiates the necessity of adopting harmonized standards and AFIR provisions as mandatory for national implementation and establishing an interagency coordination mechanism involving the Ministry for Communities, Territories and Infrastructure Development, the Ministry of Energy, the State Inspectorate of Architecture and Urban Development (DIAM), and the State Energy Supervision Authority. The proposed measures are aimed at developing a coherent system of technical regulation and supervision, strengthening institutional cooperation, and enhancing the transparency, cybersecurity, and operational reliability of the EVCI sector. These efforts will contribute to Ukraine’s gradual integration into the European energy and transport ecosystem and support the long-term goals of sustainable mobility and energy efficiency.